Public Order in Practice Recognition and Application of Foreign Arbitral Awards - Haykyants, Armen (Bulletin of Yerevan University C: Jurisprudence, 2022)
The scientific article discusses modern aspects of the application of the institution of a public policy clause in the field of recognition and enforcement of decisions of international commercial arbitration based on a co-analysis of foreign and international legal experience.The article discusses that approaches to the application of the institution of public policy cannot be static, they are subject to certain dynamics in connection with the generation of new approaches and theories in the legal doctrine. The author concludes the scientific article with the conclusion that when recognizing and applying foreign arbitral awards, there is a basis for applying public policy in case of conflict with a number of imperative norms of domestic law, based on the philosophical conviction that quantitative changes lead to qualitative changes.
Keywords: imperative norm; public policy clause; doctrine; jurisprudence; convention; national law; foreign arbitration decisions